2021
DOI: 10.1108/ijrdm-02-2020-0040
|View full text |Cite
|
Sign up to set email alerts
|

Digital touchpoints and multichannel segmentation approach in the life insurance industry

Abstract: PurposeDigital technology is revolutionizing insurance distribution allowing the insurer companies to reach customers via multichannel. The aim of this study is to segment potential customers of life insurance based on their information search, purchasing channels and personal characteristics in the digital environment.Design/methodology/approachThe study uses cross-sectional research survey. In total, 422 questionnaires were collected through a convenience sample of the Romanian population. The data was segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Similarly, Alt et al ( 2021 ) found an inverse U-shaped relationship between age and choice of digital channels for very complex products such as life insurance. This can be explained by the lack of financial literacy and the resulting need for information among the youngest insurance customers and the lack of experience with digital channels and the resulting perception of channel risks by the oldest customers (Alt et al 2021 ). These findings lend further support to the argument that customer characteristics influence channel choice only indirectly due to the diversity of needs, perceptions, situations, and contexts that characterize the approach of individual customers to a channel.…”
Section: Analysis and Findingsmentioning
confidence: 89%
See 1 more Smart Citation
“…Similarly, Alt et al ( 2021 ) found an inverse U-shaped relationship between age and choice of digital channels for very complex products such as life insurance. This can be explained by the lack of financial literacy and the resulting need for information among the youngest insurance customers and the lack of experience with digital channels and the resulting perception of channel risks by the oldest customers (Alt et al 2021 ). These findings lend further support to the argument that customer characteristics influence channel choice only indirectly due to the diversity of needs, perceptions, situations, and contexts that characterize the approach of individual customers to a channel.…”
Section: Analysis and Findingsmentioning
confidence: 89%
“…Very young customers, however – children aged 6 to 12 years – may view online channels critically and prefer offline channels for shopping (Boulay et al 2014 ); this may be due to the greater importance of other needs, such as enjoyment-seeking, among this group, or to varying perceptions of channel attributes (for example, children may find physical stores easier to navigate than online channels), or to situational aspects which inhibit the use of certain channels, such as a lack of access to online payment options. Similarly, Alt et al ( 2021 ) found an inverse U-shaped relationship between age and choice of digital channels for very complex products such as life insurance. This can be explained by the lack of financial literacy and the resulting need for information among the youngest insurance customers and the lack of experience with digital channels and the resulting perception of channel risks by the oldest customers (Alt et al 2021 ).…”
Section: Analysis and Findingsmentioning
confidence: 89%
“…Firstly, perceived ease of use can be defined as “the degree to which a person believes that using a technology will be effortless” (Castillo and Bigne, 2021, p. 879). By specifically focusing on the impact of ease of technology, and in particular mobile apps and services, on the customers' behaviours and intention, literature has widely investigated this connection in different sectors (Alt et al. , 2021; Bhatt, 2022; Mew and Millan, 2021; Shim et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Starting from education and information research, where AI's goal is to improve teacher effectiveness and student engagement [11], to healthcare, where the potential of AI to offer medical diagnosis in areas such as radiology, its importance was highlighted by many specialists [12]. At the same time it has applications for several fields such as mobility [13], insurance companies [14] or the energy sector [15]. The future development of AI promises to allow humans to focus on design and integration activities, while AI will assist these activities, offering significant efficiencies while controlling and monitoring processes in real time [16].…”
Section: Artificial Intelligence and Consumersmentioning
confidence: 99%